Cardiac consequences of intermittent hypoxia: a matter of dose? A systematic review and meta-analysis in rodents - Elise Belaïdi; Charles Khouri; Olfa Harki; Sébastien Baillieul; Gilles Faury; Anne Briançon‐Marjollet; Jean‐Louis Pépin; Claire Arnaud (2022)
Intermittent hypoxia (IH) is considered to be a major contributor to obstructive sleep apnoea-related cardiovascular consequences. The present meta-analysis aimed to assess the effects of IH on cardiac remodelling, function and infarct size after myocardial ischaemia across different rodent species and IH severities.Relevant articles from PubMed, Embase and Web of Science were screened. We performed a random effect meta-analysis to assess the effect of IH on myocardium in rodents by using standardised mean difference (SMD). Studies using rodents exposed to IH and outcomes related to cardiac remodelling, contractile function and response to myocardial ischaemia-reperfusion were included. 5217 articles were screened and 92 were included, demonstrating that IH exposure induced cardiac remodelling, characterised by cardiomyocyte hypertrophy (cross-sectional area: SMD=2.90, CI (0.82-4.98), I2=94.2%), left ventricular (LV) dilation (LV diameter: SMD=0.64, CI (0.18-1.10), I2=88.04%), interstitial fibrosis (SMD=5.37, CI (3.22-7.53), I2=94.8) and apoptosis (terminal deoxynucleotidyl transferase dUTP nick end labelling: SMD=6.70, CI (2.96-10.44), I2=95.9). These structural changes were accompanied by a decrease in LV ejection fraction (SMD=-1.82, CI (-2.52--1.12), I2=94.22%). Importantly, most of the utilised IH protocols mimicked extremely severe hypoxic disease. Concerning infarct size, meta-regression analyses highlighted an ambivalent role of IH, depending on its severity. Indeed, IH exposure with inspiratory oxygen fraction (FIO2 ) <7% was associated with an increase in infarct size, whereas a reduced infarct size was reported for FIO2 levels above 10%. Heterogeneity between studies, small study effect and poor reporting of methods in included articles limited the robustness of the meta-analysis findings.This meta-analysis demonstrated that severe IH systematically induces cardiac remodelling and contractile dysfunction in rodents, which might trigger or aggravate chronic heart failure. Interestingly, this meta-analysis showed that, depending on stimulus severity, IH exhibits both protective and aggravating effects on infarct size after experimental ischaemia-reperfusion procedures.